2021
DOI: 10.1136/bmjdrc-2020-001865
|View full text |Cite
|
Sign up to set email alerts
|

Associations between grip strength and incident type 2 diabetes: findings from the UK Biobank prospective cohort study

Abstract: IntroductionGrip strength has been associated with chronic diseases and mortality. However, current evidence of the association between grip strength and incident type 2 diabetes mellitus (T2DM) is controversial. The aim of this study was to investigate the associations of absolute and relative grip strength with incident T2DM and whether these associations differ by sociodemographic, lifestyle and adiposity-related factors.Research design and methodsThis was a prospective cohort study of 166 894 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…34 Therefore, our findings support this negative association but with a longer follow-up time. On top of this, the current work confirmed the negative association between relative grip strength and incident T2D, seen previously, 35 in the largest prospective cohort study so far.…”
Section: Discussionsupporting
confidence: 90%
“…34 Therefore, our findings support this negative association but with a longer follow-up time. On top of this, the current work confirmed the negative association between relative grip strength and incident T2D, seen previously, 35 in the largest prospective cohort study so far.…”
Section: Discussionsupporting
confidence: 90%
“…This study also found a strong relationship between type 2 DM and age and body mass index. 5 Increases in fasting glucose are inversely correlated with grip strength, according to earlier research. A study with 1664 people conducted in the US found no correlation between grip strength and 2hPG in either men or women, but a significant inverse association between fasting glucose and grip strength in males but not in women.…”
Section: Discussionmentioning
confidence: 79%
“…In a cohort study, the relationship between relative muscle mass (i.e., total skeletal muscle mass per body weight) and the risk of incident type 2 DM was stronger in young and middle-aged adults (<50 years) [ 4 ]. In a UK biobank prospective cohort study, the association between low grip strength per body weight and the risk of type 2 DM incidence was stronger in individuals aged <55 years [ 20 ]. A Japanese study on the relationship between relative HGS and prediabetes incidence showed a stronger inverse relationship in young adults (<40 years) than in older adults [ 48 ].…”
Section: Discussionmentioning
confidence: 99%